Influence of chronic toxoplasmosis on some human personality factors - Flegr, J; Hrdý, I (Folia parasitologica, 1994)
An effect of parasites on host behaviour was tested on the toxoplasma-human model. Three hundred and thirty-eight (338) people were assessed with Cattell's personality questionnaire and then tested for Toxoplasma gondii infection with a delayed type hypersensitivity test for Toxoplasma. A highly significant correlation between chronic toxoplasmosis and two personality factors (G-Low Superego Strength and L-Protension) was found (p = 0.0032 and 0.0020, respectively). A correlation of the intensity of the personality factor-shifts with the duration of the infection (estimated from antibody titer) suggests that toxoplasmosis induces the shift in human personality, rather than the personality factors G and L influence an acquisition rate of Toxoplasma gondii infection.
Keywords: dospělí; Animals; Female; Personality; Toxoplasmosis; Adult; ženské pohlaví; Adolescent; Cattell Personality Factor Questionnaire; lidé; pozdní přecitlivělost; Toxoplasma; osobnost; Sex Factors; Hypersensitivity, Delayed; protilátky protozoální; Male; Antibodies, Protozoan; Aged; sexuální faktory; Catellův osobnostní dotazník 16PF; chronická nemoc; toxoplazmóza; lidé středního věku; senioři; zvířata; mužské pohlaví; Chronic Disease; Middle Aged; mladiství; Humans